2004
DOI: 10.1016/s0002-9440(10)63289-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of TGF-β/Smad3 Signaling Modulates Skin Fibrosis in a Mouse Model of Scleroderma

Abstract: Transforming growth factor-beta (TGF-beta) is a potent stimulus of connective tissue accumulation, and is implicated in the pathogenesis of scleroderma and other fibrotic disorders. Smad3 functions as a key intracellular signal transducer for profibrotic TGF-beta responses in normal skin fibroblasts. The potential role of Smad3 in the pathogenesis of scleroderma was investigated in Smad3-null (Smad3(-/-)) mice using a model of skin fibrosis induced by subcutaneous injections of bleomycin. At early time points,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
169
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(184 citation statements)
references
References 65 publications
13
169
0
2
Order By: Relevance
“…Although studies by our group [12] and others [36] have shown the capacity of TGF-β1 to activate FAK in certain cell types, a role for SMAD3 in mediating this effect has not been previously demonstrated. The requirement for SMAD3 in FAK activation is consistent with a role for SMAD3 in myofibroblast differentiation both in-vitro [37,38] and in-vivo [39][40][41].…”
Section: Discussionsupporting
confidence: 73%
“…Although studies by our group [12] and others [36] have shown the capacity of TGF-β1 to activate FAK in certain cell types, a role for SMAD3 in mediating this effect has not been previously demonstrated. The requirement for SMAD3 in FAK activation is consistent with a role for SMAD3 in myofibroblast differentiation both in-vitro [37,38] and in-vivo [39][40][41].…”
Section: Discussionsupporting
confidence: 73%
“…In contrast, scar tissue from control mice injected with IgG antibodies contained a high frequency of very small-diameter fibrils (less than 40 nm), similar to what is found in models of cutaneous fibrosis. [20][21][22] Scars from mice injected with anti-VEGF antibodies contained a lower frequency of the small-diameter fibrils (0-40 nm) and a higher frequency of fibrils within the normal range (41-80 nm) compared with control scars. The results suggest that neutralization of VEGF not only reduced the amount of scar tissue formed (Figure 6), but also improved the quality of the scar tissue that did form by shifting the collagen fibril distribution to a state more closely resembling normal skin (Figure 7).…”
Section: Vegf Blockade Influences the Organization Of Scar Tissuementioning
confidence: 98%
“…Collagen fibril diameter measurements have been used previously to evaluate the degree of cutaneous fibrosis. [20][21][22] Three normal skin samples and six scar samples from each treatment group, all from different mice, were used for analysis. Each micrograph was divided into four parts for analysis and fibrils from four micrographs per sample were measured.…”
Section: Electron Microscopymentioning
confidence: 99%
“…Together, these studies support the concept that the actions of TGF-b and specific signaling pathways, including downstream mediators expressed in reactive stroma, is an important area for further study. In addition, although the role of Smad3-mediated TGF-b signaling in tissue fibrosis or wounding has been studied (Roberts et al, 2003;Lakos et al, 2004), it is not known whether Smad3 mediates TGF-b induction of angiogenesis and reactive stroma during carcinoma progression. Accordingly, in order to more clearly define the complicated regulation of carcinogenesis by TGF-b action in stroma, the purposes of this study were to determine whether Smad3-mediated TGF-b signaling is a key pathway in cancerassociated stroma and to subsequently assess candidate downstream mediators of TGF-b/Smad3 biological action.…”
Section: Introductionmentioning
confidence: 99%